Wskaźniki do monitoringu realizacji polityki Unii Europejskiej - wybrane zagadnienia - Markowska, Małgorzata (Indicators for EU policies implementation monitoring - selected problems, 2006)
The article presents an attempt to assess the implementation ofthe European Union requirements related to the provision of statistical data for international comparisons by Polish public statistics, for which sets of thematic indicators, including sustainable development ones, are used. The European Union countries, including Poland, have to assess the level of informational and methodological compatibility in this area. Polish position, at the background of other EU countries, was presented with reference to the level of sustainable development indicators, divided into ten thematic groups.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1129, s. 417-436